Simulasi Prakiraan dan Klasifikasi Hujan Wilayah Kota Jakarta dengan Metode Decision Tree - Prakosa, Arif Ega; Fawaid, Ahmad; Nusantara, Irkhas; Amri, Faisal; Saifudin, Aries (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Rain is a natural occurrence that occurs in the hydrological and climatic circulation. Based on the ups and downs of the hydrological circulation, one of the sources of water is rain. rain is very useful in life, because rain can meet the needs of water for living creatures. However, rain can also cause floods. A flood tragedy can cause loss and casualties. Then our activities are checking the forecast simulation forecast and rain classification using the accurate decision tree method. We take forecast and classification data because the weather in DKI Jakarta is currently very difficult to predict. Next, we use a decision tree for data mining with a dataset spanning 5 years from 2011-2015. The problem here is the weather in DKI Jakarta which is very difficult to predict.